Opportunities and Challenges in Engaging Citizens in the Co-Production of Infrastructure-based Services in Australia - Wiewiora, A.; Keast, R.; Brown, Kerry (Routledge, 2015)
Research and practice have observed a shift towards service-oriented approaches that depend on input from citizens as co-producers of services. Yet in the delivery of public infrastructure the focus is still on managing assets rather than services. Using a Policy Delphi approach, we found that although experts advocate service-centric approaches guidelines and policies lack a service-centric perspective. Findings revealed a range of impediments to effective stakeholder involvement. The paper contributes to co-production and new public governance literature and offers directions for public infrastructure decision-makers to support and reconnect disengaged government–citizen relations, and determine ways of understanding optimal service outcomes.